If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -2x(3x + -1)(4x + -3) Reorder the terms: 0 = -2x(-1 + 3x)(4x + -3) Reorder the terms: 0 = -2x(-1 + 3x)(-3 + 4x) Multiply (-1 + 3x) * (-3 + 4x) 0 = -2x(-1(-3 + 4x) + 3x * (-3 + 4x)) 0 = -2x((-3 * -1 + 4x * -1) + 3x * (-3 + 4x)) 0 = -2x((3 + -4x) + 3x * (-3 + 4x)) 0 = -2x(3 + -4x + (-3 * 3x + 4x * 3x)) 0 = -2x(3 + -4x + (-9x + 12x2)) Combine like terms: -4x + -9x = -13x 0 = -2x(3 + -13x + 12x2) 0 = (3 * -2x + -13x * -2x + 12x2 * -2x) 0 = (-6x + 26x2 + -24x3) Solving 0 = -6x + 26x2 + -24x3 Solving for variable 'x'. Remove the zero: 6x + -26x2 + 24x3 = -6x + 26x2 + -24x3 + 6x + -26x2 + 24x3 Reorder the terms: 6x + -26x2 + 24x3 = -6x + 6x + 26x2 + -26x2 + -24x3 + 24x3 Combine like terms: -6x + 6x = 0 6x + -26x2 + 24x3 = 0 + 26x2 + -26x2 + -24x3 + 24x3 6x + -26x2 + 24x3 = 26x2 + -26x2 + -24x3 + 24x3 Combine like terms: 26x2 + -26x2 = 0 6x + -26x2 + 24x3 = 0 + -24x3 + 24x3 6x + -26x2 + 24x3 = -24x3 + 24x3 Combine like terms: -24x3 + 24x3 = 0 6x + -26x2 + 24x3 = 0 Factor out the Greatest Common Factor (GCF), '2x'. 2x(3 + -13x + 12x2) = 0 Factor a trinomial. 2x((1 + -3x)(3 + -4x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333Subproblem 3
Set the factor '(3 + -4x)' equal to zero and attempt to solve: Simplifying 3 + -4x = 0 Solving 3 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4x = 0 + -3 -4x = 0 + -3 Combine like terms: 0 + -3 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75Solution
x = {0, 0.3333333333, 0.75}
| x-5/x-3=2y-7 | | 2log^3x=5 | | -16t^2+40t+11=0 | | 1.6m-4.8=-1.6 | | 6=5/4x | | -2x+3y = 1 | | 20y^2= | | 3x+3y = 9 | | 2x*(3-x)*(2x-5)=0 | | 3xy+4x-12=0 | | 12x+15=5-10x | | 0=2p(3p+5) | | 9n(2n-1)=0 | | 3^(3x-1)=1/9√3 | | x^2+2x-5x^2+16x-5= | | (2x)+(0.5x)+(0.25x)=12 | | (3k-4)(2k-3)=0 | | -7w+5(w+3)=7 | | (2x)+(0.5x)+(0.75x)=12 | | r+6=18 | | (5c-3)(7c+6)= | | 4(x-2)-7x=1 | | Y(y-1)(y+2)=0 | | 33/20 | | 2x+0.5x+0.25x=12 | | 7.15=5.5u | | 4x/8y= | | 4.9=0.6 | | 700(1000)+1200x=1000000 | | 32=8s | | 0=(4x-1)(x-1) | | a=3.14(63)(63) |